Environmental Education in South African Schools: The Role of Civil Society Organizations - Benjamin Damoah; Emmanuel Olusola Adu (Research in Social Sciences and Technology- OpenED Network, 2022)
Environmental education (EE) is an integrated component of the South African Curriculum and Assessment Policy Statement (CAPS) document. Pro-EE civil society organisations are actively involved in the implementation of EE policies in schools. The roles played by civil society organisations contribute to the trajectory of practical environmental programmes. This study adopted an interpretive paradigm, a qualitative approach, and a phenomenological design anchored on Bronfenbrenner's philosophical view of human development. One Pro-EE civil society organisation and two respondents were purposefully sampled. Semi-structured interviews and documents were tools employed to collect qualitative data and results were analysed thematically. The study revealed that Pro-EE civil society organisations play a pivotal role which includes; equipping learners to live sustainably, teachers’ professional development, policy formulation, and implementation that actualizes the CAPS document's objectives. The study recommended that the South School Act be amended to make EE policy mandatory. The department of basic education (DBE) should provide sufficient resources to Pro-EE civil society organisations to expand Eco-Schools project-based initiatives in schools regardless of the geographical location.